Elastyczność kontroli poznawczej a dwa układy sygnałowe u człowieka - Mun, Mariya; Berdibayeva, Sveta; Kozhamzharova, Dariyakul; Satiyeva, Sholpan; Mursaliyeva, Agaisha; Baizhumanova, Bibianar (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2016)
Aim of the study: The authors attempt to determine the relationship between flexibility of cognitive control and features of the nervous system in the context of two human signal systems. Material and methods : The authors used the Stroop test, the method of determining the balance of the first and the second signal systems in the context of visual memory, and two heuristic tasks: the verbal task “Swahili” and the visual-figurative task “Observer in the square”. Results: There were no direct correlations between flexible cognitive control and the first/second signal systems, or their balance. However, an important connection between the second signal system and the predominance of the verbal (semantic-conceptual) method of processing information. The results of the correlation analysis have proven the existence of a link between flexible cognitive control and successful solutions of heuristic tasks. In the group of “Rigid” subjects, the successful solution of tasks is associated with a dominant manner of the processing of the information, and the presentation of a particular task. Conclusions : The results obtained demonstrate a link between flexible cognitive control and successful solutions of heuristic tasks. They also point to a relationship between solving visual-figurative tasks and sensory-perceptual (perceptual-motor) methods of processing information. There were no direct correlations between flexible cognitive control and the first/second signal systems or their balance.